2009
DOI: 10.1097/aci.0b013e3283294038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental tobacco smoke and active tobacco smoking on the development and outcomes of asthma and rhinitis

Abstract: Several deleterious effects have been described in asthma because of smoking: accelerated decline in lung function, more severe symptoms, impairment in quality of life and diminished therapeutic response to steroids. The harmful effect of tobacco smoking is not only on asthma but also on rhinitis playing a role in disease outcomes. Tobacco exposure can influence innate immunity diminishing innate production of antigen-presenting cells cytokines, as well as an impaired response to toll-like receptor ligands. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 39 publications
0
46
0
2
Order By: Relevance
“…It contains .4,500 compounds. Out of them, o250 chemicals are known to be toxic and .50 can cause cancer [8].…”
Section: Indoor Air Pollutants and Relative Sourcesmentioning
confidence: 99%
“…It contains .4,500 compounds. Out of them, o250 chemicals are known to be toxic and .50 can cause cancer [8].…”
Section: Indoor Air Pollutants and Relative Sourcesmentioning
confidence: 99%
“…Studies in Scotland and in the United States have shown that 40% of 11-year-old children 4 and 5-year-old children 5 live with a smoker. Exposure to environmental tobacco smoke increases the incidence and severity of asthma, 6 and children are particularly susceptible to the deleterious effects of such exposure. 7 In the United States, more than 200,000 episodes of childhood asthma per year have been attributed to parental smoking.…”
mentioning
confidence: 99%
“…On the otherhand, innate immunity is impaired by tobacco exposure as well (26,27). Although several reports exist on ETS as a risk factor for having allergic diseases, scarce information is available regarding allergic rhinitis (8). While, smoking was found not to worsen the symptoms of allergic rhinitis, it has been demonstrated to be a significant related risk of incidence of asthma in patients with AR (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports exist on ETS as a risk factor for having allergic diseases, scarce information is available regarding allergic rhinitis (8). While, smoking was found not to worsen the symptoms of allergic rhinitis, it has been demonstrated to be a significant related risk of incidence of asthma in patients with AR (8,9). Moreover, there was no evidence that active smoking increased the risk of AR, but a significant relation was reported between passive smoking and AR in a meta-analysis (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation